KOMUNIKASI ANTARPRIBADI ANAK PEREMPUAN DENGAN FATHERLESS BEHAVIOR (Studi Fenomenologi Kualitas Hubungan Komunikasi dengan Lawan Jenis) - Clara Puspita (2023)
This research is motivated by the fact that among the world, Indonesia ranks third as a fatherless country. Fatherlessness itself is a condition where a child grows up without feeling the role of a father in their life, both physically and psychologically. This research aims to find out how the interpersonal communication patterns and parenting patterns of a father towards his daughter shape the daughter's communication patterns with the opposite sex. The type of research used is descriptive qualitative with a phenomenological approach and uses primary and secondary data sources. The analysis technique in this research uses the Colaizzi and Moustakas method. The selection of Fatherless female informants aged 21 years was carried out using purposive sampling. The results of the research found that the father's parenting style has the biggest role in forming a daughter's character and developing the child's social soft skills, including communication with the opposite sex. The conclusion of this research is that the parenting style of fathers towards fatherless women, ineffective communication between fatherless women and their fathers, and the attachment style of fatherless women make a significant contribution to the lack of balance in communication between fatherless women and partners of the opposite sex which causes women to be fatherless. experiencing cognitive dissonance. However, when communicating with friends of the opposite sex, fatherless women succeed in achieving communication balance and achieving cognitive consistency due to the influence of other factors, namely factors of social rejection and acceptance.